PEMBUATAN ETANOL DARI BUAH SALAK (Salacca Zalacca) YANG TIDAK LAYAK KONSUMSI - Yasin, Lukman; Jura, Minarni Rama; Supriadi, Supriadi (Universitas Tadulako, 2013)
Salak is a inclusive of into erudite tribe Moraceae name is a salacca zalacca in English named is a snake fruit and one of fruit type which is at most planted in the tropics. One of potency from of salak which improper consume that is exploited permanent upon which making ethanol, where glucose can be exploited as ethanol, because in it contain elements of carbon,hydrogen and oxygen. which is do not consume that is damage storey level 90. The purpose of this research is to cultivate salak which improper consume as raw material for making etanol by fermentation process and to determine the level of ethanol produced from salak which improper consume. In this research yeast fermentation is used with tape, NPK fertilizer and urea fertilizer. Starter used by 20 mL each of three erlenmeyer. The starter and then fermented for 5, 8, 11 and 14 days ago on distillation. After the distillation was measured levels of ethanol, the reaction with Na metal, solubility in water, density measuremen and measure pH ethanol. Then the analysis show a 5 day fermentation obtained 13.8%, ethanol content weight of 0.991 g/mL and pH 5.02. Fermentation for 8 days derived ethanol content of 10.79%, density 0.989 g/mL and pH 4.21. Fermentation for 11 days gained ethanol content 6%, weight of 0.982 g/mL and pH 3.04. And fermentation obtained 2.20%, density 1.002 g/ml and pH 2.25.